(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2022)
Background: Stroke is an acute onset of neurological dysfunction due to an abnormal cerebral vascular circulation with resulting signs and symptoms that corresponds to focal area of brain. The most common characteristics of MCA stroke are contra lateral spastic hemiparesis, motor and sensory disturbance of face, motor weakness of upper extremity and lower extremity with upper limb more affected than lower limb. Constraint induced movement therapy (CIMT) involves ipsilesional limb restraint with training of paretic arm to overcome this learned disability by restraining the unaffected extremity and training the affected extremity. Aims and objectives of the study: To observe and analysis the effect of Constrained Induced Movement Therapy on hand function of chronic stroke patients. Data Analysis & Results: Shows that the pre and post intervention values of variable functional arm reach in chronic stroke patients of this study. In that mean values of pre and post intervention of functional arm reach were 19.0 cm and 23.0 cm respectively. Results of significance p value were p≤0.05 explained that after constrained induced movement therapy intervention to the subjects the functional arm reach was improved statistically. Conclusion: This study concluded that Constraint Induced Movement Therapy (CIMT) shall have statistically significant improvement on hand function of functional arm reach distance in adult hemiplegic patients.